Italian visual dictionary - Petito, Guilia; Reid, Lauren; Riccardo, Patrizia; Stevenson, Anna (Collins, 2019)
A photographic guide to the key words and phrases in Italian. This attractive pocket-sized book is a perfect travel companion and provides a practical guide to Italy and Italian language and culture. Everyday words are arranged in themes with carefully selected up-to-date images to illustrate key words and phrases, and an English and Italian index help you to find words quickly as you learn. 3,000 essential words and phrases for modern life in Italy are at your fingertips with topics covering food and drink, home life, work and school, shopping, sport and leisure, transport, technology, and the environment. Great care has been given to represent modern Italian culture and enhance your experience of Italy and its people, including customs, celebrations, and festivals.